FREQUENCY OF POST-CORONARY ARTERY BYPASS GRAFT (CABG) THROMBOCYTOPENIA AND ITS ASSOCIATED COMPLICATIONS - Waleed Shahzad Ali; Muhammad Zaid Ali; Ahmad Mahmood; Salman Farsi; Muhammad Wasim Sajjad; Dr Imran (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: A frequent hematological side effect after coronary artery bypass grafting (CABG), especially in patients having cardiopulmonary bypass (CPB), is thrombocytopenia. Although its precise prognostic importance is still up for debate, severe thrombocytopenia may put patients at risk for complications like stroke, acute kidney damage (AKI), and bleeding. The purpose of this study was to ascertain the prevalence of thrombocytopenia following CABG and evaluate its correlation with significant postoperative complications in a Pakistani tertiary cardiac institution.Methods: From June to December 2022, a descriptive case series was carried out at the Rehman Medical Institute in Peshawar. Non-probability consecutive sampling was used to enroll seventy-four adult patients undergoing urgent or elective isolated CABG. A platelet count